Outsourcing Contracts in Public Administration: dynamics of using the linked account at the Regional Labor Court of Minas Gerais (Research, Society and Development, 2020)
The outsourcing of services presents itself as a management tool in the search for greater public efficiency. However, the default situation of the contracted companies is recurrent with respect to the labor amounts owed to their employees, which can lead to the accountability of the contracting public agency. In this context, in an attempt to align the interests involved, the linked account was created. It is a control instrument that seeks to guarantee the rights of outsourced workers, as well as to protect the Public Administration from eventual subsidiary responsibility. In the light of the agency's theory, the general objective of this work was to analyze the dynamics of using the linked account in outsourcing contracts. Specifically, it was intended to identify the benefits, critical points and difficulties arising from the option for the instrument. For this, the correlation between the theoretical framework and the empirical view was traced, through a case study within the Regional Labor Court of the 3rd Region. After a content analysis, it was demonstrated that the use of the linked account can be costly for both sides of the contractual relationship, but that its adoption is not inappropriate in all situations. Therefore, it was concluded that the linked account must be organized in order to maximize its benefits and reduce its costs. Otherwise, the current trend of expanding outsourcing, in order to make administrative performance more efficient, is harmed by the burden of contractual monitoring.